Direct formation and site-selective elaboration of methionine sulfoximine in polypeptides. Issue 47 (21st November 2022) - Ding, Yuxuan; Pedersen, Simon S.; Lin, Alex; Qian, Ruoyu; Ball, Zachary T.
Abstract : Sulfoximines are emerging moieties for medicinal and biological chemistry. This work describes the late-stage incorporation of methionine sulfoximine residues into polypeptides and chemoselective subsequent elaboration of NH-sulfoximines. Abstract : Sulfoximines are emerging moieties for medicinal and biological chemistry, due in part to their efficacy in selective inhibition of amide-forming enzymes such as γ-glutamylcysteine synthetase. While small-molecule sulfoximines such as methionine sulfoximine (MSO) and its derivatives are well studied, structures with methionine sulfoximine residues within complex polypeptides have been generally inaccessible. This paper describes a straightforward means of late-stage one-step oxidation of methionine residues within polypeptides to afford NH-sulfoximines. We also present chemoselective subsequent elaboration, most notably by copper(ii )-mediated N–H cross-coupling at methionine sulfoximine residues with arylboronic acid reagents. This development serves as a strategy to incorporate diverse sulfoximine structures within natural polypeptides, and also identifies the methionine sulfoximine residue as a new site for bioorthogonal, chemoselective bioconjugation.